1988
DOI: 10.1159/000226624
|View full text |Cite
|
Sign up to set email alerts
|

Hexose Monophosphate Shunt Enzymes in Lung Tumors from Normal and Glucose-6-Phosphate-Dehydrogenase-Deficient Subjects

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate, dehydrogenase the key enzymes of the hexose monophosphate shunt pathway, were measured in both surrounding and tumoral lung tissues from normal and G6PD-deficient subjects. A significant increase of these enzymatic activities in tumoral tissue was found not only in G6PD-normal patients, but also in G6PD-deficient patients with very low or nonmeasurable G6PD activity in both erythrocytes and normal lung tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…As we mentioned earlier, large numbers of studies revealed elevated G6PD activities were found in various cancers [8][9][10][11][12][13][14][15][16][17], overexpression of G6PD can promote tumorigenesis [5] and silencing G6PD expression by siRNA decreased tumor-cell proliferation and enhanced apoptosis [7]. Consistent with this, Wang-Ni Tian et al found that G6PD activity correlate with cell proliferation and cells overexpressing G6PD have a higher proliferation rate than that expressing only endogenous G6PD [26].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As we mentioned earlier, large numbers of studies revealed elevated G6PD activities were found in various cancers [8][9][10][11][12][13][14][15][16][17], overexpression of G6PD can promote tumorigenesis [5] and silencing G6PD expression by siRNA decreased tumor-cell proliferation and enhanced apoptosis [7]. Consistent with this, Wang-Ni Tian et al found that G6PD activity correlate with cell proliferation and cells overexpressing G6PD have a higher proliferation rate than that expressing only endogenous G6PD [26].…”
Section: Discussionmentioning
confidence: 65%
“…Li et al demonstrated that silencing G6PD expression by siRNA decreased tumorcell proliferation and enhanced apoptosis [7]. And more importantly, elevated G6PD activities have been found in various human cancers, including bladder cancer [8], renal cell carcinoma [9], ovarian cancer [10], fibrosarcoma [11], breast cancer [12], endometrial carcinoma [13], cervical caricinoma [14], prostatic carcinoma [15,16], and lung carcinoma [17]. However, there is no large sample report about the expression and clinical significance of G6PD in human gastric cancer progression and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, both G6PD and 6PGD have been shown to be increased in cervical carcinoma (32, 34, 36), as well as in lung tumors (82). The critical role of 6PGD in cancer cell proliferation has been described in non-small cell lung carcinoma.…”
Section: -Phosphogluconate Dehydrogenasementioning
confidence: 99%
“…1). Although protective against oxidative stress, this response may enable the rapid proliferation of cancer cells even in adverse environments (10,25).…”
Section: Oxidative Stress and Neonatal Lung Injurymentioning
confidence: 99%
“…Nevertheless, the same genes downstream of Nrf2 may alter cellular metabolic fate and enable lung cancer cells to grow more rapidly (25). This will be discussed briefly in a later section.…”
Section: Figmentioning
confidence: 99%